Pengaruh Fasilitas Dan Persepsi Harga Terhadap Kepuasan Konsumen Pada Hotel Angkasa Garden Pekanbaru - Sri Dewi, Diana; Saputri, Marlinda (Sekolah Tinggi Ilmu Ekonomi Riau, 2025)
Hotel Angkasa Garden Pekanbaru is one of the three star hotels in Pekanbaru City. This hotel offers affordable prices and is also equipped with adequate facilities, from parking, garden, free breakfast, sakura swimming pool, Ballroom and Metting Room which are comfortable for family and office events. The research was conducted at Angkasa Garden Hotel Pekanbaru on Jl. Dr. Setia Budi No. 107. This research was conducted for six months from October 2022 to March 2023. The population in this study were consumers who had stayed at the Angkasa Garden Hotel Pekanbaru. Then the technique used is simple random sampling technique, namely taking sample members from the population randomly without regard to strata in the population. The number of samples taken in this study were 100 consumers. This research was conducted for six months from October 2022 to April 2023. The population in this study were consumers who had stayed at the Angkasa Garden Hotel Pekanbaru. Then the technique used is simple random sampling technique, namely taking sample members from the population randomly without regard to strata in the population. The number of samples taken in this study were 100 consumers. Based on the hypothesis and analysis of the results of the study, it can be concluded that F arithmetic F table is 164.457 3.09 with sig 0.000 0.05. This indicates that capital regression can be used to simultaneously test the effect of independent variables on the dependent variable, namely facilities and price perceptions simultaneous effect on consumer satisfaction. The results of this study state that the sig value for the influence of X1 on Y is 0.000 0.05 and the t value is 5.376 1.98472 so it can be concluded that H1 is accepted, which means that facilities have a significant influence in determining the level of customer satisfaction. The results of this study state that the sig value for the effect of X2 on Y is 0.000 0.05 and the t value is 4.850 1.98472, so it can be concluded that H2 is accepted which means that there is an influence of X2 on Y.